2021
DOI: 10.1002/anie.202115503
|View full text |Cite
|
Sign up to set email alerts
|

Proton/Electron Donors Enhancing Electrocatalytic Activity of Supported Conjugated Microporous Polymers for CO2Reduction

Abstract: Metal phthalocyanines (MePc) hold great promise in electrochemical reduction of CO 2 to value-added chemicals, whereas the catalytic activity of MePc-containing polymers often suffers from a limited molecular modulation strategy. Herein, we synthesize an ultrathin conjugated microporous polymer sheath around carbon nanotubes by an ionothermal copolymerization of CoPc and H 2 Pc via the Scholl reaction. Given the H 2 Pc-mediated regulation in the synthesis, Co II metal is well preserved in the form of single at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 43 publications
(23 reference statements)
2
35
0
Order By: Relevance
“…41 Guo and coworkers recently reported the phthalocyanines polymerized through solid ion thermal utilizing Scholl reaction (Figure 5A) with carbon nanotubes as the substrates, which could provide both CoN 4 sites and H 2 Pc sites for CO 2 RR. 42 As is shown in Figure 5B, in the phthalocyanine catalysts, CoN 4 could serve as the active sites to interact with CO 2 molecules while H 2 Pc sites could boost CO 2 RR as the donors of protons and electrons. As a result, the performance of phthalocyanines could reach the FE of 97% with a large current density of >200 mA cm -2 .…”
Section: Applications In Electrochemical Reactionsmentioning
confidence: 98%
“…41 Guo and coworkers recently reported the phthalocyanines polymerized through solid ion thermal utilizing Scholl reaction (Figure 5A) with carbon nanotubes as the substrates, which could provide both CoN 4 sites and H 2 Pc sites for CO 2 RR. 42 As is shown in Figure 5B, in the phthalocyanine catalysts, CoN 4 could serve as the active sites to interact with CO 2 molecules while H 2 Pc sites could boost CO 2 RR as the donors of protons and electrons. As a result, the performance of phthalocyanines could reach the FE of 97% with a large current density of >200 mA cm -2 .…”
Section: Applications In Electrochemical Reactionsmentioning
confidence: 98%
“…For example, the proton donor H 2 Pc can facilitate the selective CO 2 reduction to CO on a conjugated composite microporous CoPc/H 2 Pc polymer catalyst (Figure 8d ). [ 119 ] The measurement of kinetic isotope effect (KIE) indicated that the rate‐determining step was the proton transfer process, and the addition of the proton donor, H 2 Pc, decreased the KIE value from 4.0 to 1.77, signifying accelerated proton transfer. The proton donor H 2 Pc lowered the energy barrier of the reduction of *CO 2 to the *COOH intermediate and the further reduction of *COOH to *CO.…”
Section: Electron Transfer and Proton Coupling On The Biomimetic Phot...mentioning
confidence: 99%
“…Many pioneering efforts have also demonstrated that atomically dispersed active sites anchored onto NC substrates can effectively enhance ORR performances, indicating a preferable application of NC substrates [38][39][40][41][42][43][44], for instance, isolated single-atom Fe anchored on N-doped porous carbon and Cu-Zn clusters on porous NC [45][46][47]. Furthermore, transition metal-nitrogen-carbon (TM-N-C)-based catalysts have attracted widespread interest for CO 2 RR electrocatalysis because their 3d electron orbitals endow metal-N x (x denotes N coordination number) sites with efficient intrinsic CO 2 RR activity [48][49][50]. Therefore, the rational design of bifunctional electrocatalysts containing dual-core active sites for both CO 2 RR and ORR has significant practical applications.…”
Section: Introductionmentioning
confidence: 99%